Misi Penyebaran Agama Kristian Terhadap Komuniti Islam pada Era Penjajahan Portugis di Melaka, 1511–1641 : Christian Religious Mission towards the Muslim Community during the Portuguese Colonial Era in Malacca, 1511–1641 - Hong, Tew Yen; Mohd Noor , Arba’iyah; Ngadiran, Siti Nor Aisyah (Journal of Al-Tamaddun, 2025)
Generally, before the arrival of the Portuguese in Malacca, the Malay community was predominantly Muslim. This is because Islam had long been established in Malacca and several Malay regions. After the Portuguese conquered Malacca in 1511, they made various efforts to spread Christianity among the local population. This article aims to provide a more comprehensive historical perspective on the Portuguese conquest of Malacca, with a specific focus on the efforts, challenges, and impact of spreading Christianity among local inhabitants. This research is a qualitative historical study, emphasizing analysis of primary sources such as Portuguese records, as well as secondary sources such as journal articles and books. The research materials were also obtained from the archives, public higher education institution libraries, and online journal databases. The finding shows that although the spread of Christianity during the Portuguese era in Malacca faced challenges, efforts were still made to influence the Muslim community. However, the acceptance of Christianity among Muslims remained limited due to their strong faith in Islam.